The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/pme.12773
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Opioid Use and Dependence among People Living with Chronic Pain: Associations Observed within the Pain and Opioids in Treatment (POINT) Cohort

Abstract: In this population of people taking opioids for CNCP, consumption of higher doses was associated with increased risk of problematic behaviors, and was more likely among people with a complex profile of physical and mental health problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 47 publications
5
77
0
Order By: Relevance
“…Another consideration is that the subjects included in our analysis were all enrollees of private or employer‐based insurance plans, and they tend to have fewer complications and lower health care utilization compared with patients enrolled on publicly insured health plans . Another study on a cohort of mainly publicly insured adult patients with SCD indicated that the median dose of daily OME was 6 mg, which is similar to our observation in this study and lower than the dose used to treat other pain syndromes, such as chronic non‐cancer pain …”
Section: Discussionsupporting
confidence: 77%
“…Another consideration is that the subjects included in our analysis were all enrollees of private or employer‐based insurance plans, and they tend to have fewer complications and lower health care utilization compared with patients enrolled on publicly insured health plans . Another study on a cohort of mainly publicly insured adult patients with SCD indicated that the median dose of daily OME was 6 mg, which is similar to our observation in this study and lower than the dose used to treat other pain syndromes, such as chronic non‐cancer pain …”
Section: Discussionsupporting
confidence: 77%
“…A significant minority of our sample reports concurrent use of more than one opioid and many participants report that they also use OTCs. These findings are consistent with previous findings of opioid use in other chronic pain patients [55]. Similar to other pain conditions, the unemployed [41,56] and older individuals [57,58] were more likely to report opioid use.…”
Section: Physical and Psychological Burden In Opioid Userssupporting
confidence: 83%
“…For example, data from the United States suggest that the non-medical use of prescription opioids is most common among younger people [41]. In Australia, younger males have been identified as most at risk of developing opioid dependence among people prescribed opioids for chronic pain [42]. Furthermore, unintentional deaths due to oxycodone toxicity are higher among males between the ages of 35 and 44 [43].…”
Section: Discussionmentioning
confidence: 99%